Quantitative research in education - Gorard, Stephen; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2008)
This set conveys a picture of education as lifelong and society-wide and as a process which is affected by time, place policy, structure, and individual characteristics. The articles combine a mix of methodical approaches alongside a mix of top-name authors from around the world.
v. 1. Key issues in education research -- v. 2. Key techniques for education research -- v. 3. Debates in the conduct of education research.
Specialized.
Description based on print version record.
Includes bibliographical references.
Keywords: Education -- Research; Education -- Research -- Methodology; Educational statistics; Electronic books